A feminist look at social psychology / Una mirada feminista a la psicología social. Issue 2 (4th May 2019) - Ferrer-Pérez, Victoria A.
Abstract: This theoretical revision starts from the consideration that the gender perspective constitutes a critical, explanatory and alternative vision that comes from feminism and generates an analysis framework that takes into consideration and pays attention to the differences and inequalities between women and men in any activity or area of social development, research or public policies. The objective of this revision is to provide clues to understanding what gender or feminist social psychology is. To this end, firstly, we briefly describe feminist theoretical assumptions and the gender or feminist perspective, which constitute its starting point, and secondly, we analyse what it means to integrate these principles into psychology.